DMP-1-mediated Ghr gene recombination compromises skeletal development and impairs skeletal response to intermittent PTH - Liu, Zhongbo (FASEB J, 2016)
Bone minerals are acquired during growth and are key determinants of adult skeletal health. During puberty, the serum levels of growth hormone (GH) and its downstream effector IGF-1 increase and play critical roles in bone acquisition. The goal of the current study was to determine how bone cells integrate signals from the GH/IGF-1 to enhance skeletal mineralization and strength during pubertal growth. Osteocytes, the most abundant bone cells, were shown to orchestrate bone modeling during growth. We used dentin matrix protein (Dmp)-1-mediated Ghr knockout (DMP-GHRKO) mice to address the role of the GH/IGF axis in osteocytes. We found that DMP-GHRKO did not affect linear growth but compromised overall bone accrual. DMP-GHRKO mice exhibited reduced serum inorganic phosphate and parathyroid hormone (PTH) levels and decreased bone formation indices and were associated with an impaired response to intermittent PTH treatment. Using an osteocyte-like cell line along with in vivo studies, we found that PTH sensitized the response of bone to GH by increasing Janus kinase-2 and IGF-1R protein levels. We concluded that endogenously secreted PTH and GHR signaling in bone are necessary to establish radial bone growth and optimize mineral acquisition during growth.—Liu, Z., Kennedy, O. D., Cardoso, L., Basta-Pljakic, J., Partridge, N. C., Schaffler, M. B., Rosen, C. J., Yakar, S. DMP-1-mediated Ghr gene recombination compromises skeletal development and impairs skeletal response to intermittent PTH.